Growth and Elemental Stoichiometry of the Ecologically-Relevant Arctic Diatom Chaetoceros gelidus: A Mix of Polar and Temperate - Schiffrine, Nicolas; Tremblay, Jean-Éric; Babin, Marcel (Frontiers in Marine Science, 2020)
In the wake of modest surface blooms that occur at the onset of the growth season in the nitrogen-poor surface waters of the Beaufort Sea, subsurface chlorophyll maxima (SCM) develop and persist within the nutrient-rich halocline. Algal communities of these SCM can realize a major portion of annual net primary production and are often dominated by the widespread diatom Chaetoceros gelidus in coastal waters. In order to assess how changing growth conditions at the SCM may affect the biological carbon pump, grazer nutrition, and dissolved nutrient inventories across the transpolar Pacific-Atlantic conduit, the elemental stoichiometry of a C. gelidus strain (RCC2046) isolated from the Beaufort Sea and its response to the availability of light and different forms of nitrogen (N) were examined in the laboratory. The cells were grown in semi-continuous batch cultures at 0°C under sub-saturating (LL; 5.5 μmol photons m−2 s−1) or saturating irradiance (HL; 200 μmol photons m−2 s−1) and with ammonium (NH4+), nitrate (NO3-) or urea as sole N form in nutrient-replete conditions. The growth rate, cell size, maximum quantum efficiency of photosystem II (Fv/Fm) and the concentrations of chlorophyll a (Chl a), biogenic silica (Si) and particulate N, phosphorus (P), and organic carbon (C) were measured during the exponential growth phase. Despite a clear response of volumetric quotas to N form, the growth rates and elemental ratios of the cells were unaffected by N form in the two irradiance treatments. Elemental ratios were affected by light and the responses were remarkably similar to those observed for temperate diatoms. Overall, this study shows that the growth and elemental composition of C. gelidus in the Arctic Ocean are highly resistant to changes in nitrogen form at near-freezing temperatures and suggests that this diatom possesses the ability to remain competitive despite ongoing environmental changes.